Sounding the changes: Clients report on GIM music used in cardiac rehabilitation. (November 2021) - Short, Alison
Highlights: The Bonny Method of Guided Imagery and Music (GIM) promotes client self-report. Client self-report of musical experiences during GIM has rarely been studied. Narrative semiotic qualitative analysis explored client experiences during GIM. The music influenced imagery process, feelings, joining together and communication. Findings inform further understandings of the role of music in GIM practice. Abstract: As an established specialty within the field of music therapy, the Bonny Method of Guided Imagery and Music (GIM) forms an integrated music psychotherapy of value of many clients. However, the role of music has rarely been systematically studied from the client's perspective. This study reports on client's references to the music within a larger study of the use of GIM in recovery from cardiothoracic surgery. Six participants (aged 55–69 years) undertook six weekly GIM sessions at two major hospitals, starting 6–15 weeks postoperatively. Audio-recorded sessions were transcribed and analysed within a narrative semiotic qualitative approach. Within the emergent grand theme, "Sounding the changes" the four sub-themes were: 1) Directing the action, 2) Evoking feelings, 3) Voicing together, and 4) Unfolding communication. Self-reported responses and relationships to music were informative about the patient journey, providing further insights for clinical practice about the individualised role of music within this important therapeutic modality.